Impressive performance of proton-conducting solid oxide fuel cells using a first-generation cathode with tailored cations. Issue 32 (30th July 2019) - Xu, Xi; Wang, Huiqiang; Ma, Jinming; Liu, Wenyun; Wang, Xianfen; Fronzi, Marco; Bi, Lei
Abstract : Tailoring the first-generation cathode La0.5 Sr0.5 FeO3− δ with Pr-doping brings new life to the cathode for proton-conducting solid oxide fuel cells. Abstract : Tailoring the first-generation cathode La0.5 Sr0.5 FeO3− δ with Pr-doping successfully expands the cathode reaction active area and thus leads to a doubled fuel cell power output, which brings new life to the cathode for proton-conducting solid oxide fuel cells.